The World Crisis, 1915. - Churchill, Winston S. (Winston Churchill World Crisis Collection., 2013)
The second volume in Churchill's "outstandingly readable history of the First World War" (David Fromkin, author of A Peace to End All Peace). This second volume in Winston Churchill's five-volume series The World Crisis is by far the most personal'dealing frankly with Churchill's failures as a military leader and his ultimately unsuccessful battle to break the European deadlock. After the disastrous Gallipoli landings on the Dardanelles, Winston Churchill served for several months as commander of the 6th Battalion of the Royal Scots Fusiliers. During this time, he served on one of the most violent stretches of the front lines, making a total of 36 courageous expeditions into No Man's Land. In this chapter of his "remarkable" eyewitness account (Jon Meacham), Churchill provides an unflinching narrative of a particularly challenging time in World War I and in his own career'providing fascinating insight into the mental and psychological challenges faced by a major historical leader